Effective Da'wah in the Era of Society 5.0 : The Perspective of Students in Indonesian State Islamic Higher Education - Tahir, M. (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study describes da’wah that is relevant to the era of Society 5.0 from the perspective of State Islamic Higher Education (PTKIN) students in Indonesia. The effective da’wah was raised based on the communication theory by Harold Lasswell, namely the characteristics of da'i (preacher), the media of da’wah, the theme of da’wah, the methods of conveying, and the effects of da’wah. Therefore, this study used a qualitative descriptive approach with observations, interviews, and documentation techniques to collect data. Informants were PTKIN students. This study found several patterns including, first, da’i need to have characteristics such as the obligatory qualities of the Prophet, be exemplary, have charismatic demeanors, and be easy to understand; second, social media is the media of da’wah most favored by students; third, the theme of da’wah must be following the situation and conditions of mad’u (listeners) and be easy to accept and understand; fourth, the methods of conveying da’wah messages are varied and combined; and fifth, the effects of da’wah is not only in the form of information or knowledge but also awareness and feeling—and is followed up with action and practice.